LEUKOSIT INFEKSI BAKTERI SISTEMIK - Meita Hendrianingtyas; MI. Tjahjati DM (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
Patients in intensive care unit (ICU) have a high risk for systemic bacterial infection. Serum procalcitonin (PCT) known as a markerto predict bacterial infection, systemic inflammation responsse (SIRS) or sepsis. Another simple and easy indicator is by using leucocytecount-differential count, absolute neutrophyl count (ANC), and immatur/total (I/T) neutrophyl ratio. The aim of this study was toknow the comparation of the leucocyte count-differential count, ANC, and I/T ratio with procalcitonin serum value in patients suspectto systemic bacterial infection at ICU. A cross sectional study on 20 patients suspected with systemic bacterial infection in ICU. The datawas classified in 3 groups based on PCT serum value: group A (< 0.5 ng/mL), group B (0.5–2 ng/mL) and group C (> 2 ng/mL). Thedata was analysed by one way ANOVA test if normally distributed, and by Kruskall-Wallis test if not normally distributed. Significancywas confirmed at p < 0.05. A post hoc and Mann-Whitney test performed on a significant result. The frequency of group A was 3 (15%),group B = 5 (25%), and group C = 12 (60%). There is no significant difference on leucocyte count in 3 groups (p = 0.953), neutrophylI/T ratio (p = 0.259), ANC (p = 0.91), eosinophyl count (p = 0.287), segment neutrophyl (p = 0.094), and monosit (p = 0.152).There was a difference on lymphocyte count (p = 0.01) between group C with group A and group B and there was a difference on staffneutrophyl count (p = 0.029) and total neutrophyl count (p = 0.003) between group A with group B and C (p = 0.029). In this studywere found differences on lymphocyte, staff neutrophyl and total neutropyl count to the PCT value